The Protective Effect and Mechanism of Dexmedetomidine on Diabetic Peripheral Neuropathy in Rats - Zhang, Yan-zhuo; Zhou, Zhong-cheng; Song, Chun-yu; Chen, Xia (Frontiers in Pharmacology, 2020)
Objective: To investigate the role of dexmedetomidine (DEX) in the inhibition of diabetic peripheral neuropathy (DPN) and the protection in the nerve damage. Methods: 80 male Sprague-Dawley (SD) rats were randomly allocated to four groups: the Control group(C group), DPN model group (DPN group), dexmedetomidine-treated group (DEX group) and the yohimbine treated group (YOH group). DPN was induced by intraperitoneal administration of streptozocin (STZ) (35 mg/kg). The body weights, blood glucose level, mechanical withdrawal threshold (MWT), thermal withdrawal latency (TWL), the motor and sensory nerve conduction velocities (MNCV and SNCV) of sciatic nerve were measured. Then the sciatic nerve was isolated for HE staining and immunohistochemical staining. The oxidative stress makers such as malondialdehyde (MDA), superoxide-dismutase (SOD) and glutathione peroxidase (GSH-Px), apoptosis related cytokines such as Bax, Bcl-2 and caspase-3 were estimated. Results: There was no significant difference of the blood glucose and body weight among the DPN group, DEX group and YOH group. HE staining showed that DEX treatment can ameliorate the damage of sciatic nerve cells. In the DPN group, MWT, TWL, MNCV and SNCV were significantly reduced compared with the C group (P < 0.05). In DEX group rats, MWT, TWL, MNCV and SNCV were increased significantly (P < 0.05) compared with the DPN group and YOH group rats. Lower SOD and GSH-Px, and higer MDA were found in the DPN group compared with the C group (P < 0.01), and DEX treatment restored SOD, GSH-px and MDA activity significantly (P < 0.01). The expression levels of Bax and Caspase-3 were increased, while that of Bcl-2 was decreased significantly in the DPN group compared with the C group (P < 0.05). In the DEX group, the expression levels of Bax and Caspase-3 were decreased significantly (P < 0.05), while that of Bcl-2 was increased significantly (P < 0.05) compared with the DPN group and the YOH group. Conclusion: The results of this study demonstrated that DEX has the inhibitory and protective effects on DPN of rats. This may be associated with its antioxidative and anti-apoptosis responses.